Social insurance and allied services : memorandum on the Beveridge Report
1943-02-10 1943 1940s 24 pages 20. and that other countries will be willing to pay whatever price we ask in order that we say provide conditions at home better than they themselves can afford for their own people. (64) On this subject of the Social Services which other countries provide for their population, the following excerpt from the Report, enumerating the services provided in 30 different countries (Appendix F, page 287) shows how pre-eminent Great Britain already is :- "Taking all the 30 countries together, 20 have compulsory sickness insurance, 24 have some form of contributory pension, 8 have unemployment insurance. Three countries only in the 30 - New Zealand, Bulgaria and Poland - make provision against all the three risks of sickness, old age and unemployment. That is to say, three countries only aim at covering all the principle forms of social insecurity as fully as Britain. The United States has no sickness insurance; Germany has now no unemployment insurance'. The Report does not show, so far as Bulgaria and Poland are concerned, either the scale of the benefits which their Social Services provide or the conditions attached to the drawing of them, but, so far as New Zealand is concerned, the Report (page 290) points out that "apart from the contributory pensions which are to reach their full rate in 1968, all the benefits in New Zealand are subject to a means test". It may also be pointed out that it is only within recent years that the U.S.A. has instituted Unemployment Insurance and Old Age Pensions Insurance; that those Services do not cover the same scope as ours do; that it has attached to its Unemployment Insurance more rigorous conditions than those which we have in our country today; and that Health Insurance, as above shown, is as yet unknown in U.S.A. No doubt U.S.A. will develop its Social Service Insurance system but it would seem, in present circumstances, appropriate that our two countries should try to keep some common pace with each other in this as in other great adventures. (65) Without seeking to do more than examine the feasibility of Sir William Beveridge's estimate of a post-war unemployment figure of 10%, it seems to us that, before committing this country to the "Beveridge" plan, the following features of our post-war situation and of the "Beveridge" plan itself call for careful consideration as factors which may make unreliable the estimate upon which the plan is so largely based :- (a) The/ 200/B/3/2/C216/5/50